2009
DOI: 10.1002/jor.21027
|View full text |Cite
|
Sign up to set email alerts
|

Influence of the ratio of particulate autogenous bone graft/platelet-rich plasma on bone healing in critical-size defects: A histologic and histometric study in rat calvaria

Abstract: The purpose of this study was to analyze histomorphometrically the influence of the ratio of particulate autogenous bone (AB) graft/platelet-rich plasma (PRP) on bone healing in surgically created critical-size defects (CSD) in rat calvaria. Fifty rats were divided into five groups: Group C (control), Group AB, Group AB/PRP-50, Group AB/PRP-100, and Group AB/PRP-150. A 5-mm diameter critical-size defect was created in the calvarium of each animal. In Group C, the defect was filled by blood clot only. In Group … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
26
1
4

Year Published

2010
2010
2020
2020

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 29 publications
(35 citation statements)
references
References 29 publications
(44 reference statements)
3
26
1
4
Order By: Relevance
“…Several studies 7,12,19,23,30,31 in the literature have described the tissue reactions, both in soft and hard tissues using the materials employed in this research; however, there are only a few works in the literature that compared the use of the MTA and the BCP in isolation or in association for the healing of standardized critical bone defects.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Several studies 7,12,19,23,30,31 in the literature have described the tissue reactions, both in soft and hard tissues using the materials employed in this research; however, there are only a few works in the literature that compared the use of the MTA and the BCP in isolation or in association for the healing of standardized critical bone defects.…”
Section: Discussionmentioning
confidence: 99%
“…The amalgam was then applied to mark the center of the surgical wound. 23 After carefully removing the incised portion of the calvaria with the aid of a Molt dissector, the BCP was added to the wound of 20 animals (Straumann® BoneCeramic, Institut Straumann AG, Basel, Switzerland) as per the instructions of the manufacturer, filling the entire calvaria cavity (up to the edge of the defect). In 20 other samples, the MTA (MTA -Angelus®, Angelus Industry of dental products S/A, Londrina, Paraná, Brazil) was applied according to the instructions of the manufacturer.…”
mentioning
confidence: 99%
“…During this process, the rate of PLDLA scaffold degradation was similar to that of bone formation since no signs of impaired bone growth, such as necrosis and fibrous capsule formation around the implanted material, were observed. These results indicated a good interaction at the interface between newly bone formed and the implanted PLDLA construct 33 . Although the histological analysis has revealed that the PLDLA constructs were biocompatible with bone tissue and were not cytotoxic during tissue repair, we assumed that some factors related to the porogen-leaching method used to manufacture the scaffolds may have affected the interactions between the PLDLA constructs and native tissue, thereby preventing better PLDLA scaffold-cell interaction and bone formation.…”
Section: Histological Analysis Of Pldla Scaffolds Implanted In Ratsmentioning
confidence: 67%
“…From the other authors, we learned, that high concentrations of PRP produce negative effects such as suppression of proliferation of osteoblasts [46,47]. Three and a half fold to 8 fold concentrations of platelets in PRP compared to baseline seem to have the best effect.…”
Section: Methodsmentioning
confidence: 99%
“…Nagata et al [47] and Mariano et al [51] worked on a rat calvarium model using critical sized defects (CRD) of 5mm in diameter. The rat calvarium model however is established as 8 - 9 mm in literature [47,51].…”
Section: Methodsmentioning
confidence: 99%